2022
DOI: 10.3390/ijms23136994
|View full text |Cite
|
Sign up to set email alerts
|

An Eleven-microRNA Signature Related to Tumor-Associated Macrophages Predicts Prognosis of Breast Cancer

Abstract: The dysregulation of microRNAs (miRNAs) has been known to play important roles in tumor development and progression. However, the understanding of the involvement of miRNAs in regulating tumor-associated macrophages (TAMs) and how these TAM-related miRNAs (TRMs) modulate cancer progression is still in its infancy. This study aims to explore the prognostic value of TRMs in breast cancer via the construction of a novel TRM signature. Potential TRMs were identified from the literature, and their prognostic value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 104 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…According to biological information database, TLR was related to macrophage polarization, then microRNAs including let‐7b , let‐7e , let‐7i , miR146 , miR105 , miR223 and miR147 which regulated TLR and its downstream NF‐κB signaling pathway were selected for PCR verification and let‐7b , miR146 and miR147 were confirmed to be significantly up‐regulated in LAMs from AML‐refractory mice (Figure 3C). It was reported that let‐7b participated in the TAMs mediated growth of prostate cancer and breast cancer, 9,10 however its role was not reported in hematologic malignancies. Therefore, let‐7b was selected as the research target to modify LAM reprogram.…”
Section: Resultsmentioning
confidence: 99%
“…According to biological information database, TLR was related to macrophage polarization, then microRNAs including let‐7b , let‐7e , let‐7i , miR146 , miR105 , miR223 and miR147 which regulated TLR and its downstream NF‐κB signaling pathway were selected for PCR verification and let‐7b , miR146 and miR147 were confirmed to be significantly up‐regulated in LAMs from AML‐refractory mice (Figure 3C). It was reported that let‐7b participated in the TAMs mediated growth of prostate cancer and breast cancer, 9,10 however its role was not reported in hematologic malignancies. Therefore, let‐7b was selected as the research target to modify LAM reprogram.…”
Section: Resultsmentioning
confidence: 99%
“…miRNAs comprise small noncoding RNA molecules that regulate gene expression post-transcriptionally and are involved in the onset, progression, and metastasis of breast cancer [ 19 , 20 ]. Recent studies reported that a diagnostic miRNA signature can be employed to assess tumor aggressiveness, drug response, and outcomes in patients with breast cancer [ 19 , 21 , 22 ]. Furthermore, miRNA expression profiles have been reported to be different for each molecular subtype of breast cancer [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several breast cancer prognosis-prediction models are available. Generally, these tools have been developed based on the selection of prognostic genes based on bulk RNA-seq data and internal validation [21][22][23]. Typically, internal validation is not sufficient to fully validate a model.…”
Section: Discussionmentioning
confidence: 99%